Sustainable pilot scale disperse dyeing in a waterless silicone medium dyeing system for no discharge of wastewater. (25th October 2021) - Cheng, Wenqing; Pei, Liujun; Saleem, Muhammad Asad; Zhu, Lei; Wang, Jiping
Abstract: Clean dyeing technologies for polyester textiles, particularly waterless dyeing, have been studied extensively in recent decades. In the present work, a new waterless dyeing technology, the silicone medium dyeing, for polyester textiles had been investigated. The dyeing process of polyester textile in the silicone medium was optimized by determining the dyeing temperature, holding time, type and dosage of dye accelerator. The dye uptake of disperse dye and the fastness properties of the dyed polyester were equivalent to those of conventional water-bathed dyeing. After dyeing, polyester textile had a better color levelness. From the TGA and XRD results, it can be proved that silicone medium has no adverse effects on the fiber and can be used as a dyeing medium. The influence of the increase of halogen in the diazotized component on the affinity, dye uptake, diffusion coefficient, and other parameters was obtained by analyzing the dye uptake of C.I. Disperse Orange 44 and C.I. Disperse Yellow 163. These parameters formulate guidelines for the selection of disperse dyes for silicone medium dyeing system. To verify the feasibility of industrialization, pilot-scale dyeing was carried out. The results showed that, as compared to aqueous dyeing, higher colorfastness and better color levelness were obtained from silicone media. Therefore, this eco-friendly dyeing technology has considerable potential to become a mainstream dyeing method in the foreseeable future. Highlights: The use of water is avoided throughout the dyeing and washing process. Dye uptake can be adjusted by accelerant. Superior fastness and leveling. The diversified styles of textiles are developed and achieved a pilot test.